A numerical investigation into the aerodynamic effect of pressure pulses on a tunnel ventilation fan. (May 2014) - Cardillo, Lucio; Corsini, Alessandro; Delibra, Giovanni; Rispoli, Franco; Sheard, Anthony G
Tunnel ventilation fans are subjected to pressure pulses as a consequence of trains passing the ventilation shafts within which they are installed. These pressure pulses alter the volume flow rate through a ventilation fan, and consequently the static pressure field around fan blades. Today's trains typically travel through railway tunnels faster than has been the historic norm. Additionally, platform screen doors are now a standard feature of metro systems. Both result in the trains involved inducing larger pressure pulses than industrial fan designers have traditionally assumed. Although tunnel ventilation fan in-service failures are rare, engineers increasingly associate those failures with new or renovated tunnel systems with larger pressure pulses. Consequently, we require insight into the aerodynamic and mechanical consequences that occur with subjecting a tunnel ventilation fan to a pressure pulse. In the research reported in this paper, the authors model the pressure pulse induced by a train in a tunnel system as a rapidly changing fan volume flow rate. The authors computed the fan operating point by means of a large eddy simulation with a one-equation sub-grid scale turbulence model. The authors undertook the computation using the open source computational fluid dynamic code OpenFOAM. An analysis of the computational results provides an insight into the effects of turbulent structures that develop within the fan blade passage. The analysis indicates that a pressure pulse too brief to drive a tunnel ventilation fan into stall still results a doubling of the unsteady aerodynamic and mechanical forces to which the blade is subjected. A doubling of unsteady mechanical forces as a consequence of a pressure pulse constitutes an increase significant enough to contribute to the tunnel ventilation fan's in-service mechanical failure.